2004
DOI: 10.1002/apj.5500120416
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Heat Transfer Process of Horizontal Anode Baking Furnace

Abstract: IntroductionLarge amounts of carbon anodes are consumed in the aluminum industry. Anodes are made of petroleum coke held together by a pitch binder. They must be baked to a given temperature of about 1000 to 1200°C at a very low heating rate (10-15"Ch) in order to obtain the appropriate mechanical and electrical properties required for their use in electrolync cells [l, 21. This baking process occurs in a horizontal or vertical ring h a c e , which is built as a chain of sections arranged in a ring shape. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Since for most outputs of interest, linearity was satisfactory, it is possible to use Eq. (18) to predict the outputs of interest for a given set of inputs, as well as the variance of the outputs for given variances of the inputs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since for most outputs of interest, linearity was satisfactory, it is possible to use Eq. (18) to predict the outputs of interest for a given set of inputs, as well as the variance of the outputs for given variances of the inputs.…”
Section: Discussionmentioning
confidence: 99%
“…The second category is 'overall models' where the ABF is treated as a counterflow heat exchanger: the gas is flowing from inlet to outlet and the solids are "moving" in the opposite direction at a speed corresponding to a section length divided by the fire time (roughly 5m/24h) [8][9][10][11][12][13][14][15][16][17][18] . The core of these models gas along the furnace.…”
Section: Kinetic Parameters Variability Within Normal Distributions a H2mentioning
confidence: 99%
“…11 It is reported that the spatial temperature distributions during the baking process in ABF would determine the properties of anode. 12 The structure of the typical ABF is shown in Figure 1. 13 In this layout, the anode blocks are placed in the pits and covered by the packing coke, as shown in Figure 1B.…”
Section: Introductionmentioning
confidence: 99%
“…Among the aforementioned processes, the baking process in the anode baking furnace (ABF) has the huge influence on the anode quality 11 . It is reported that the spatial temperature distributions during the baking process in ABF would determine the properties of anode 12 …”
Section: Introductionmentioning
confidence: 99%
“…In mid-1990's, a full 3D transient model was reported [10]. Later on, many models of varying complexity, but similar in nature to these early works have been published [11][12][13][14]. Mathematical modelling has become a key tool in the improvement furnace operation and design.…”
Section: Introductionmentioning
confidence: 99%